MEDIA POSTER PEMBELAJARAN TAJWID UNTUK SANTRI DI TPA - Santoso, Iman; Nuari, Feby Nabiilah; Khairunnisa, Siti; Syahrullah, Syahrullah (Journal Education and Government Wiyata, 2024)
This research was motivated by the fact that the average Al-Qur'an reading ability of students at the Al-Falah Musholla TPA with poster media still lacked understanding of the science of recitation. Maybe the presence of poster media in learning recitation can make it easier for students to understand the material on recitation of the law of nun or tanwin and repeat it at home at any time. This research was carried out by collecting data through interviews and literature study by producing a media poster for learning tajwid for students at Al-Falah Musholla TPA. How to read the Koran with hijaiyyah letters, both reading idzhar halqi, ikhfa, iqlab, idgham bighunnah, and idgham bilaghunnah. Because we misread the letters of the Qur'an, it will affect the meaning of the verse. The method used is lectures, practice looking for examples in the Al-Qur'an. So the results of this activity are very useful, especially for those who have never learned to read the Al-Qur'an according to the rules of reciting the science of recitation and for those who have learned to remember it.